Identification of the potential active site of the septal peptidoglycan polymerase FtsW. - Ying Li; Adrien Boes; Yuanyuan Cui; Shan Zhao; Qingzhen Liao; Han Gong; Eefjan Breukink; Joe Lutkenhaus; Mohammed Terrak; Shishen Du (PLoS Genetics)
SEDS (Shape, Elongation, Division and Sporulation) proteins are widely conserved peptidoglycan (PG) glycosyltransferases that form complexes with class B penicillin-binding proteins (bPBPs, with transpeptidase activity) to synthesize PG during bacterial cell growth and division. Because of their crucial roles in bacterial morphogenesis, SEDS proteins are one of the most promising targets for the development of new antibiotics. However, how SEDS proteins recognize their substrate lipid II, the building block of the PG layer, and polymerize it into glycan strands is still not clear. In this study, we isolated and characterized dominant-negative alleles of FtsW, a SEDS protein critical for septal PG synthesis during bacterial cytokinesis. Interestingly, most of the dominant-negative FtsW mutations reside in extracellular loops that are highly conserved in the SEDS family. Moreover, these mutations are scattered around a central cavity in a modeled FtsW structure, which has been proposed to be the active site of SEDS proteins. Consistent with this, we found that these mutations blocked septal PG synthesis but did not affect FtsW localization to the division site, interaction with its partners nor its substrate lipid II. Taken together, these results suggest that the residues corresponding to the dominant-negative mutations likely constitute the active site of FtsW, which may aid in the design of FtsW inhibitors.